Heart-lung transplantation for patients under 10 with cystic fibrosis. Issue 1 (1st January 1997) - Balfour-Lynn, I M; Martin, I; Whitehead, B F; Rees, P G; Elliott, M J; de Leval, M R
Abstract : The outcome of patients with cystic fibrosis aged under 10 years referred for heart-lung transplantation assessment (n=58) was determined and compared with older children (n=109). Similar proportions were placed on to the active waiting list (64% v 71%) and received transplants (35% v 31%). Three year post-transplantation survival figures were also similar (41% v 46%), as were the figures for overall survival for those placed on to the active list (27% v 29%). Paediatricians should not be deterred from referring younger patients for transplantation.